Technology and policy options for reducing India's import dependence on edible oils - S. J., Balaji; Sharma, Purushottam; P., Venkatesh; Kapoor, Shreya (Indian Council of Agricultural Research, 2022)
India heavily depends on imports to meet its edible oil demand. In 2020-21, it imported 54% of the total edible oil demand, spending Rs. 1.17 lakh crores. Notably, most of the imports are from a few countries. About 94% of the crude palm oil and 99% of the RBD palmolein are imported from Indonesia and Malaysia; 97% of the soybean oil from Argentina and Brazil; and 97% of the sunflower oil from Ukraine, Russia, and Argentina. This means higher supply risks and price uncertainty, especially during climatic shocks, conflicts, and pandemics such as COVID-19. Uncertain supply inflates prices and erodes purchasing power, forcing governments to resort to subsidies and cash transfers to protect domestic consumers, and reduce import duties and provide other incentives for industries and importers. The surge in import bills due to rising international prices and increasing domestic support amplify fiscal deficits, curtailing investments that could have positively influenced economic growth. Enhancing domestic production capacity should help bring down import bills. The Government of India has taken several policy measures to promote oilseeds and edible oil production. The production has increased, but the demand has outpaced it, leading to a continued increase in imports. The improvements in production technology and protective tariffs could be the instruments of choice. This brief looks at the recent trends in edible oil imports and the possibilities of reducing these by increasing domestic production, adopting yield-enhancing technologies, and raising import tariffs.